2014
DOI: 10.3109/1354750x.2014.926567
|View full text |Cite
|
Sign up to set email alerts
|

The role of preoperative neutrophil–lymphocyte and platelet–lymphocyte ratio in patients after radical resection for gastric cancer

Abstract: The objective of this study was to investigate the impact of neutrophil-lymphocyte ratio (NLR) and the platelet-lymphocyte ratio (PLR) on the postoperative complication and long-term outcomes in patients with resectable gastric cancer (GC). A total of 377 patients who underwent curative resection for GC were enrolled. In logistic analysis, PLR (p = 0.09) was independently associated with the incidence of postoperative complication. The results of multivariate survival analysis showed the NLR and PLR were intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 21 publications
3
68
1
3
Order By: Relevance
“…CRP is an index of systemic inflammation and has been identified as a prognostic factor in patients with CRC and gastric cancer (24,25). However, serum CRP levels are not routinely assessed in the pre-operative assessment (12,14,18). Instead, NLR and PLR, calculated from leukocyte differential counts and platelet counts, respectively, are more readily available and inexpensive compared to CRP (7).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CRP is an index of systemic inflammation and has been identified as a prognostic factor in patients with CRC and gastric cancer (24,25). However, serum CRP levels are not routinely assessed in the pre-operative assessment (12,14,18). Instead, NLR and PLR, calculated from leukocyte differential counts and platelet counts, respectively, are more readily available and inexpensive compared to CRP (7).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, NLR and PLR, calculated from leukocyte differential counts and platelet counts, respectively, are more readily available and inexpensive compared to CRP (7). Notably, numerous previous studies have already indicated that an elevated NLR and PLR is associated with a poorer survival in patients with ovarian (8), breast (9,10), non-small cell lung (11), esophageal (12,13), gastric (7,14) and hepatocellular cancers (15) and CRC (2,(16)(17)(18). NLR is the ratio of the absolute neutrophil count to the absolute lymphocyte count, and therefore the association between a high NLR and a poor prognosis, as revealed in the present study, is possibly indicative of the tumor-promoting activity associated with neutrophilia in the tumor environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, in 377 patients who underwent curative resection for gastric cancer, high PLR was an independent predictive factor for worse overall survival [64]. In 162 patients diagnosed with resectable gastric cancer, high PLR correlated with decreased both overall and cancer-free survival [16].…”
Section: Plr and Survival: Prognostic Implicationsmentioning
confidence: 99%